The Chronicler's Vorlage, Kalimi verses Auld. Issue 1 (2nd January 2019) - Clancy, Frank
ABSTRACT: Graeme Auld's argument of the "Two Houses" sharing the same vorlage is rejected by Isaac Kalimi. Kalimi insists that the Chronicler used the proto-Masoretic book of Kings as his source. However, there are a number of problems not addressed by Kalimi including chronological patterns and conflicting synchronisms. There is every reason to believe that the redacted proto-Masoretic book of Kings and the book of Chronicles shared the same vorlage as Auld has argued.